Uptake and Survival of African Swine Fever Virus in Mealworm (Tenebrio molitor) and Black Soldier Fly (Hermetia illucens) Larvae - Ann Sofie Olesen; Christina Marie Lazov; Antoine Lecocq; Francesc Accensi; Annette Bruun Jensen; Louise Lohse; Thomas Bruun Rasmussen; Graham J. Belsham; Anette Bøtner (Pathogens, 2022)
Insect production offers a sustainable source of nutrients for livestock. This comes with a risk for transmission of pathogens from the insects into the livestock sector, including viruses causing serious diseases, such as African swine fever virus (ASFV), classical swine fever virus and foot-and-mouth disease virus. ASFV is known to survive for a long time within animal meat and byproducts. Therefore, we conducted experimental exposure studies of insects to ASFV using larvae of two key insect species produced for food and feed, the mealworm; Tenebrio molitor, and the black soldier fly, Hermetia illucens. The larvae were exposed to ASFV POL/2015/Podlaskie, via oral uptake of serum or spleen material from ASFV-infected pigs. Using qPCR, the amounts of viral DNA present immediately after exposure varied from ~104.7 to 107.2 genome copies per insect. ASFV DNA was detectable in the larvae of H. illucens for up to 3 days post exposure and in T. molitor larvae for up to 9 days post exposure. To assess the presence of infectious virus within the larvae and with this, the risk of virus transmission via oral consumption, pigs were fed cakes containing larvae exposed to ASFV. Pigs that consumed 50 T. molitor or 50 H. illucens virus-exposed larvae did not become infected with ASFV. Thus, it appears, that in our experimental setting, the risk of ASFV transmission via consumption of unprocessed insect larvae, used as feed, is low.